2004
DOI: 10.1038/modpathol.3800238
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of adenomatous polyposis coli gene expression, APC locus-microsatellite instability and APC promoter methylation in the progression of melanocytic tumours

Abstract: Adenomatous polyposis coli gene (APC) defects have been demonstrated for the first time in familial adenomatous polyposis. Recent reports indicate that the APC gene is an intermediary between cell adhesion molecules and the cytoskeleton and that it may function as a gatekeeper of colonic epithelial proliferation. The objective of this study was to analyse APC's presence in lentigos, primary melanomas and melanoma metastases. By immunohistochemistry, APC was demonstrated in all lentigos, in 75 out of 88 primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…Interestingly, high levels of ␤-catenin have been observed in malignant melanomas. Furthermore, activating mutations in the ␤-catenin gene (CTNNB1), as well as genetic and epigenetic alterations of the APC gene, occur in malignant melanomas and are associated with melanoma progression (26,48,62). Thus, as in colon cancer, aberrant Wnt signaling is relevant to the genesis and progression of melanomas.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, high levels of ␤-catenin have been observed in malignant melanomas. Furthermore, activating mutations in the ␤-catenin gene (CTNNB1), as well as genetic and epigenetic alterations of the APC gene, occur in malignant melanomas and are associated with melanoma progression (26,48,62). Thus, as in colon cancer, aberrant Wnt signaling is relevant to the genesis and progression of melanomas.…”
Section: Resultsmentioning
confidence: 99%
“…BRAF mutations, often observed in cutaneous melanoma, were not found in uveal melanomas 12 13. Hypermethylation of RASSF1, RARB and APC has been identified in cutaneous melanoma 14 – 16. However, except for RASSF1 in one recent study,10 these epigenetic events have not been investigated in uveal melanoma.…”
mentioning
confidence: 94%
“…non-human primates. Rats treated with CCl 4 were used to serve as an in vivo halogenated hydrocarbon-induced liver injury model (Korabiowska et al, 2004). In the present study, CCl 4 stimulated oxidative stress, as indicated by the elevated level of TBARS and the decreased level of SOD activity in the liver of the rats, which would further induce lipid peroxidation, initial free radical damage to the hepatocyte membrane and eventually lead to the liver injury (Andus et al, 1991).…”
Section: Discussionmentioning
confidence: 96%
“…CCl 4 has been shown to induce oxidative stress, leading to lipid peroxidation and free radical production, which plays an important pathological role in liver injury (Korabiowska et al, 2004). The effect of rBPTI on lipid peroxidation products, measured as TBARS in the liver, is shown in Figure 4(a).…”
Section: Rbpti Reduces Oxidative Stress In Ratsmentioning
confidence: 99%